PENGARUH PEMBERIAN Trichoderma sp. TERHADAP PERTUMBUHAN DAN HASIL TANAMAN PAKCOY (Brass ica rapa L.) - Serli Y. Uky; Eka Citra Gayatri Kerihi, Nur Aini Bunyani (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2025)
Brassica plants or scientifically known as Brassica Rapa L. are one type of vegetable that belongs to the Brassicaceae family. Trichoderma is a genus of fungi that is found in almost all environmental conditions. This species is mostly found in soil in areas with temperate climates. This study was conducted with the aim of determining the effect of Tricoderma sp on the growth of packchoy plants, determining the effect of Tricoderma sp on the yield of packchoy plants. This research method uses a Completely Randomized Design (CRD) with one main factor, namely the application of Trichoderma sp with 4 levels of treatment. Each treatment was repeated 3 times. So there are 12 experimental units. The results of this study indicate that the treatment with the application of Trichoderma sp. (25 / 1g / / 1kg of soil) gives the best plant height, namely 31.33 cm, the number of leaves is 29.66 / leaf and fresh weight is 382.66 gr